1999
DOI: 10.1074/jbc.274.37.26209
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor (NGF)-induced Calcium Influx and Intracellular Calcium Mobilization in 3T3 Cells Expressing NGF Receptors

Abstract: The neurotrophins have been implicated in the acute regulation of synaptic plasticity. Neurotrophin-stimulated presynaptic calcium uptake appears to play a key role in this process. To understand the mechanism of neurotrophin-stimulated calcium uptake, the regulation of calcium uptake and intracellular mobilization by nerve growth factor (NGF) was investigated using NIH 3T3 cells stably transfected with either the high affinity NGF receptor p140 trk (3T3-Trk) or the low affinity NGF receptor p75 NGFR (3T3-p75)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…However, no intrinsic expression of other neurotrophic factors as like CNTF, FGF1/2, GDNF, NGF, NT3, NT4 and NT5 has been reported in NIH3T3 cells. Instead, this fibroblast cell line seem to present the ideal platform for genetical modifications for functional and structural related studies, ie calcium signalling, neurotrophic factor receptor binding, neuronal survival and bioactivity of neurotrophic factors in dose dependent manner (Dazert et al, 1998;Fryer et al, 1997;Glass et al, 1991;Jerregard et al, 2001;Jiang et al, 1999;Li et al, 2002;Wissel et al, 2008). Thus, we assume that the changes in SGC survival and neurite sprout observed in co-cultivation assays with non-modified NIH3T3 cells result from additional endogenous BDNF and/or other growth factor secreted from bystanding cells, in particular glial and satellite cells that are present in primary SGC cultures.…”
Section: Discussionmentioning
confidence: 98%
“…However, no intrinsic expression of other neurotrophic factors as like CNTF, FGF1/2, GDNF, NGF, NT3, NT4 and NT5 has been reported in NIH3T3 cells. Instead, this fibroblast cell line seem to present the ideal platform for genetical modifications for functional and structural related studies, ie calcium signalling, neurotrophic factor receptor binding, neuronal survival and bioactivity of neurotrophic factors in dose dependent manner (Dazert et al, 1998;Fryer et al, 1997;Glass et al, 1991;Jerregard et al, 2001;Jiang et al, 1999;Li et al, 2002;Wissel et al, 2008). Thus, we assume that the changes in SGC survival and neurite sprout observed in co-cultivation assays with non-modified NIH3T3 cells result from additional endogenous BDNF and/or other growth factor secreted from bystanding cells, in particular glial and satellite cells that are present in primary SGC cultures.…”
Section: Discussionmentioning
confidence: 98%
“…It has recently been shown that p75 NTR can regulate cellular calcium levels, causing an influx of calcium into the cell after NGF stimulation (68), suggesting that p75 NTR may interact with an ion channel or channel regulator. Furthermore, many studies show that membrane localization of calpain is necessary for its activation (66), which would explain the requirement for membrane attachment for Chopper killing action.…”
Section: Discussionmentioning
confidence: 99%
“…3D). Likewise, p62 down-regulation in NIH-3T3 cells expressing either p75 or TrkA receptor (20) (Fig. 3D) also abrogated NGF-induced activation of NF-B.…”
Section: P62 Is a Scaffold For Nf-b Activation By Ngf 7711mentioning
confidence: 99%